Impact of Teachers' Understanding and Merdeka Curriculum Implementation on Teacher Competence and Student Academic Performance - Sianturi, Tri Juli Ana Utami; ., Suryadi; Santoso, Budi; Fatwa, Andi Diah Sakinah (Journal of Ecohumanism, 2025)
This study aims to examine the relationships between Teachers' Understanding of the Merdeka Curriculum (TUMC), Curriculum Implementation Quality (CIQ), Teacher Competence in Developing Instructional Materials (TCDIM), and Student Academic Achievement (SAA) in Indonesian high schools. The research aims to examine how teachers' comprehension of the curriculum affects instructional material development, curriculum implementation quality, and student academic achievement. A quantitative approach was employed, involving 487 high school teachers and students from DKI Jakarta. Data were collected through questionnaires and analyzed using structural equation modeling. The study findings reveal significant positive relationships between TUMC, CIQ, TCDIM, and SAA. Specifically, TUMC positively affects both TCDIM and SAA, while CIQ directly impacts TCDIM and SAA. Additionally, TCDIM significantly predicts SAA. This study contributes to the existing literature by clarifying the critical role of teachers' curriculum understanding in shaping instructional quality and student achievement. The findings underscore the importance of investing in teacher training and professional development to enhance teachers' comprehension of the curriculum and their instructional material development skills. Furthermore, the study highlights the need for policy initiatives that improve CIQ and foster collaborative partnerships among educational stakeholders. The novelty of this study lies in its focus on the Merdeka Curriculum and its implications for educational practices and policies in Indonesia.